2014
DOI: 10.1007/s11695-014-1500-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia and Related Deficiencies 10 Years After Gastric Bypass—a Retrospective Study

Abstract: Twenty-seven percent of patients had anemia more than 10 years after RYGB. Anemia does not seem to progress with time and was less common in patients with regular medical checkups. Thus, improved long-term follow-up is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 16 publications
1
23
2
Order By: Relevance
“…In this study, postoperative iron panels were not reported, but increasing degrees of anaemia were associated with a statistically significant greater incidence of the degree of microcytosis ( P < 0.0001). The reported prevalence of iron deficiency reported by others in up to 5 years after metabolic surgery is 20% to 50% (Table ) . These results demonstrate an alarming development of iron deficiency and anaemia with longer follow‐up.…”
Section: Postoperative Iron Nutritionmentioning
confidence: 63%
“…In this study, postoperative iron panels were not reported, but increasing degrees of anaemia were associated with a statistically significant greater incidence of the degree of microcytosis ( P < 0.0001). The reported prevalence of iron deficiency reported by others in up to 5 years after metabolic surgery is 20% to 50% (Table ) . These results demonstrate an alarming development of iron deficiency and anaemia with longer follow‐up.…”
Section: Postoperative Iron Nutritionmentioning
confidence: 63%
“…Iron-deficiency anemia and vitamin B 12 deficiency after gastric bypass are well described. 23,24 Vitamin B 12 deficiency was not unexpected after sleeve gastrectomy, and it presumably relates to a reduction in intrinsic factor production after the procedure. These results, as well as the decreased vitamin A levels after gastric-bypass surgery, highlight the importance of long-term follow-up to evaluate nutritional measures, as well as the importance of ensuring that appropriate supplementation is provided to minimize the development of clinically significant nutritional deficiencies in adolescents after bariatric surgery.…”
Section: Discussionmentioning
confidence: 98%
“…In cases of post-surgery conception, specific nutritional deficiencies can affect visual acuity (vitamin A) and the development of the nervous system (vitamin B12) and neural tube (folates) [87,88]. …”
Section: Focus On Conditions Associated With Nutrient Deficienciesmentioning
confidence: 99%